2014
DOI: 10.1016/j.bioelechem.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of carbon steel by bacteria from North Sea offshore seawater injection systems: Laboratory investigation

Abstract: Influence of sulfidogenic bacteria, from a North Sea seawater injection system, on the corrosion of S235JR carbon steel was studied in a flow bioreactor; operating anaerobically for 100days with either inoculated or filtrated seawater. Deposits formed on steel placed in reactors contained magnesium and calcium minerals plus iron sulfide. The dominant biofilm-forming organism was an anaerobic bacterium, genus Caminicella, known to produce hydrogen sulfide and carbon dioxide. Open Circuit Potentials (OCP) of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…43,44 It has since been extensively elaborated to include the effect of water temperature, oxygen availability, water velocity 45 and also the influence of waterborne nutrients on particularly the longer term corrosion losses. 46,47 Recognition of these factors and their effect on the bi-modal model has permitted explanations to be offered for practical problems such as accelerated low water corrosion 48 of steel sheet piling, 49,50 channelling corrosion of water injection pipelines 51,52 and the severe pitting corrosion of mooring chains off the coast of West Africa and elsewhere. 53 In addition, the bi-modal model also has been found to be consistent with data for the marine and other atmospheric corrosion of steels, 54 corrosion of cast iron, 55 copper-nickels 56 and aluminium, 57 including for pitting corrosion.…”
Section: Models For Corrosion Loss With Timementioning
confidence: 99%
“…43,44 It has since been extensively elaborated to include the effect of water temperature, oxygen availability, water velocity 45 and also the influence of waterborne nutrients on particularly the longer term corrosion losses. 46,47 Recognition of these factors and their effect on the bi-modal model has permitted explanations to be offered for practical problems such as accelerated low water corrosion 48 of steel sheet piling, 49,50 channelling corrosion of water injection pipelines 51,52 and the severe pitting corrosion of mooring chains off the coast of West Africa and elsewhere. 53 In addition, the bi-modal model also has been found to be consistent with data for the marine and other atmospheric corrosion of steels, 54 corrosion of cast iron, 55 copper-nickels 56 and aluminium, 57 including for pitting corrosion.…”
Section: Models For Corrosion Loss With Timementioning
confidence: 99%
“…Because of the amount of debris recovered during periodic pigging operations it has been suggested that channelling corrosion could be the result of 'under-deposit' corrosion although the precise mechanisms involved remain unclear (Gregson and Hunsbedt 2011). Channelling corrosion also has been attributed to microbial influenced corrosion (MIC) (Palmer and King 2008;Heidersbach and van Roodselaar 2012 microbiological activity (Skovhus et al 2012) and laboratory studies using simulated WIP systems indicate MIC involvement (Stipanicev et al 2014). In addition, bio-samples taken periodically from coupons mounted at the upstream end of WIPs, flush with the internal pipe wall surface, show evidence of bacterial consortia.…”
Section: Introductionmentioning
confidence: 98%
“…In marine environments, corrosion is enhanced due to the intrinsic characteristics of seawater; most notably, salinity, the presence of nutrients, and the intermittency associated with the tidal variation of the water level are critical factors for the gradual damage of metallic structures, which is occasionally observed in relatively short periods of time [1][2][3][4][5]. Additionally, the presence of highly diverse bacterial communities in marine environments can promote corrosion processes [6] and has been shown to substantially increase the economic expenses, owing to direct costs for repairing or preventing the resulting damage [7][8][9]. In this context, corrosion in seawater is determined by both biotic and abiotic parameters [10]; however, the separation between these two factors is not always clear.…”
Section: Introductionmentioning
confidence: 99%